An Ultraviolet Germicidal Irradiation Autonomous Robot - Ibhaze, Augustus; Adekogbe, Favour Moyosoreoluwa (Fırat University, 2023)
Utilization of UV light for disinfection and sterilization has increased as a result of its germicidal properties; nevertheless, due to its adverse effects on the skin and eyes, this poses a risk to individuals. The demand for autonomous UV robots originates from the requirement that UV disinfection must occur without human intervention in order to minimize health risks and take advantage of UV light as a disinfection mechanism. This study focuses on the development of a UV disinfection robot that navigates autonomously via obstacle detection and avoidance using Raspberry Pi 4 model B interfaced with UV light and YOLOv4 for high touch object detection. The UV disinfection robot uses object detection to find objects that come into touch with hands frequently and successfully cleans them with UV light. The robot uses an embedded system with a Raspberry-Pi controller, motion sensors, and detects human presence because UV radiation may be harmful to humans. Without human intervention, the autonomous UV disinfection system was effective in cleaning surfaces. Based on the findings in this study, the dosimeter showed a very faint purple tint at 10, 20, and 30 minutes that ranges from 0 to 25 mJ/cm2. Between 45 and 60 minutes, and between 25 and 50 mJ/cm2, the dosimeter exhibited a vivid purple color. These results showed that even though different bacteria require different exposure durations to become inactive, a minimum disinfection time of 10 minutes is required to conduct any type of disinfection.

UV ışığının antiseptik özelliklerinin bir sonucu olarak dezenfeksiyon ve sterilizasyon amacıyla kullanımı artmıştır; ancak cilt ve gözler üzerindeki olumsuz etkileri nedeniyle bireyler için risk oluşturmaktadır. Otonom UV robotlarına olan talep, sağlık risklerini en aza indirmek ve bir dezenfeksiyon mekanizması olarak UV ışığından yararlanmak için UV dezenfeksiyonunun insan müdahalesi olmadan gerçekleşmesi gerekliliğinden kaynaklanmaktadır. Bu çalışma, yüksek temaslı nesne tespiti için UV ışığı ve YOLOv4 ile ara yüzlenen Raspberry Pi 4 model B'yi kullanarak engel tespiti ve kaçınma yoluyla otonom olarak hareket eden bir UV dezenfeksiyon robotunun geliştirilmesine odaklanmaktadır. UV dezenfeksiyon robotu, ellerle sık temas eden nesneleri bulmak için nesne algılamayı kullanır ve bunları UV ışığıyla başarılı bir şekilde temizler. Robot, Raspberry-Pi denetleyicisi ve hareket sensörleri içeren gömülü bir sistem kullanıyor ve UV radyasyonu insanlara zararlı olabileceğinden insan varlığını tespit ediyor. Otonom UV dezenfeksiyon sistemi, insan müdahalesi olmadan yüzeylerin temizlenmesinde etkili oldu. Bu çalışmadaki bulgulara göre dozimetre, 10, 20 ve 30. dakikada 0 ile 25 mJ/cm2 arasında değişen çok soluk bir mor renk tonu gösterdi. 45 ile 60 dakika arasında ve 25 ila 50 mJ/cm2 arasında dozimetre canlı mor renk sergiledi. Bu sonuçlar, farklı bakterilerin inaktif hale gelmeleri için farklı maruz kalma sürelerine ihtiyaç duymalarına rağmen, herhangi bir dezenfeksiyon türünün gerçekleştirilmesi için minimum 10 dakikalık bir dezenfeksiyon süresinin gerekli olduğunu gösterdi.
Bir Ultraviyole Antiseptik Işınlama Otonom Robo
Keywords: Electrical Engineering (Other); Elektrik Mühendisliği (Diğer)